Rapid Diagnosis of Blood Stream Infections in ICU: Recent Advances - Pangeni, Raju Prasad (Nepalese Medical Journal, 2019)
Blood stream infections and sepsis are major causes of hospitalization in most intensive care units around the globe, especially in developing countries like Nepal. Although the sepsis guidelines emphasize the role of early institution of appropriate antibiotics, it is practically challenging due to delayed turnover time of currently available diagnostic tests. Modifications in traditional blood culture methods, use of molecular techniques and availability of biomarkers have raised hope in rapid detection of blood stream infections.